Formulating Business Strategies Using SWOT and QSPM: A Qualitative Approach to Overcoming Market and Management Challenges - Illiyuni, Faridha; Moko, Wahdiyat (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – The issues faced by the Petunia Project include hindered business development due to market competition, internal management issues, and sales instability. Against this background, the research is conducted to formulate business strategies by identifying internal and external factors of the Petunia Project. This study aims to analyze the formulation of business strategies for the Petunia Project. Design/methodology/approach – The research method employed is qualitative descriptive. The analytical tools used in this study include IFE Matrix, EFE Matrix, SWOT Matrix, IE Matrix, and QSPM (Quantitative Strategic Planning Matrix). Findings – The results of this study indicate that the priority strategy that can be applied by the Petunia Project to develop its business is to utilize promotional service features on e-commerce platforms such as Live, Event Sale, Vouchers, and Free Shipping to attract potential customers. Originality/value – This study provides originality by integrating IFE, EFE, SWOT, IE Matrix, and QSPM in a single analytical framework to generate data-driven strategic priorities for a medium-scale fashion MSME, an approach that remains limited in existing literature. The research adds value by offering a comprehensive and quantifiable evaluation of strategic alternatives specifically tailored to the competitive digital marketplace in which local fashion brands operate. Furthermore, the findings contribute practical insights for MSMEs in the creative economy sector seeking to strengthen business sustainability through evidence-based strategy formulation.